K(ATP) channel openers protect rat islets against the toxic effect of streptozotocin - Kullin, M; Li, Z; Hansen, J B; Björk, E; Sandler, S; Karlsson, F A (Diabetes (New York, N.Y.), 2000)
K(ATP) channel openers protect rat islets against the toxic effect of streptozotocin. M Kullin , Z Li , J B Hansen , E Björk , S Sandler and F A Karlsson Department of Medical Sciences, Uppsala University, Sweden. Abstract We examined the influence of two K(ATP) channel openers, diazoxide and an analog (NNC 55-0118), on experimental beta-cell damage induced by streptozotocin (STZ; 0.5 mmol/l). Rat pancreatic islets were exposed to diazoxide or NNC 55-0118 for 30 min and were further incubated for 30 min after the addition of STZ. The islets were then washed and cultured for 24 h. Islets exposed to STZ alone showed extensive morphological damage, reduced glucose oxidation, low insulin content, and severely impaired glucose-stimulated insulin secretion and proinsulin biosynthesis. Islets treated with STZ in the presence of the channel openers (0.03-0.30 mmol/l) showed dose-dependent preservation of the morphology and improved glucose oxidation rates, insulin content, and secretion. NNC 55-0118 was capable of fully counteracting the STZ impairment, whereas diazoxide had a less protective effect. NNC 55-0118 did not counteract STZ-induced depression of islet NAD levels when examined 2 h after STZ exposure, which suggests that the mechanism of action by NNC 55-0118 is not through an inhibition of poly(ADP-ribose) polymerase. The results illustrate that K(ATP) channel openers can protect insulin-producing cells against toxic damage, an effect that may be of use in subjects with ongoing insulitis.